1999
DOI: 10.1046/j.1440-1703.1999.143300.x
|View full text |Cite
|
Sign up to set email alerts
|

Light, nutrients and primary productivity in Lake Biwa: An evaluation of the current ecosystem situation

Abstract: Simple correlation and multiple regression analyses were performed to examine the relationship between primary productivity and environmental factors in the north basin of Lake Biwa. The primary production rates used in the analyses were estimated monthly or bimonthly during the growing season (April–November) in 1992, 1996 and 1997 with the 13C method. Elemental (C, N and P) contents of seston were used to assess nutrient conditions. Analyses revealed that 86% of variance in depth‐integrated primary productio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 30 publications
0
30
0
1
Order By: Relevance
“…However, after 1970, total phosphorus in the surface layer of this lake tended to decrease, probably because of legal regulation of nutrient loading and the development of sewerage systems in the surrounding areas. In Lake Biwa, algal growth and primary production are limited mainly by the P supply (Urabe et al 1999). Therefore, it is unlikely that primary production, and, thus, the sinking flux of organic matter to the lake bottom, increased suddenly in 1985.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, after 1970, total phosphorus in the surface layer of this lake tended to decrease, probably because of legal regulation of nutrient loading and the development of sewerage systems in the surrounding areas. In Lake Biwa, algal growth and primary production are limited mainly by the P supply (Urabe et al 1999). Therefore, it is unlikely that primary production, and, thus, the sinking flux of organic matter to the lake bottom, increased suddenly in 1985.…”
Section: Discussionmentioning
confidence: 99%
“…However, we could not ascribe the increase in abundance of J. annandalei to an overall increase in supply of their food. It is well known for a variety of organisms that the maturation size decreases with decreasing food supply (Urabe 1991;Johnson and Widerholm 1992;Urabe and Sterner 2001). Thus, the maturation size of J. annandalei suggests that per capita food supply was kept low after 1985.…”
Section: Discussionmentioning
confidence: 99%
“…This phosphorus mineralization would be necessary for the growth of microorganisms, which are frequently limited by inorganic phosphorus (Toolan et al 1991, Coveney & Wetzel 1992. Several researchers have reported that phosphorus is an important growth-limiting factor for microorganisms, especially for phytoplankton, in the epilimnion of Lake Biwa, during stratification periods (Tezuka 1984, 1985, Frenette et al 1996, Urabe et al 1999). During our sampling period, a concentration of 23.8 µg l -1 dDNA was detected in the epilimnion.…”
Section: Discussionmentioning
confidence: 99%
“…The respiration to photosynthesis ratio from spring to autumn has been reported to be in the range of 1.2 to 2.5 for Lake Superior (26), indicating a gross heterotrophic condition. In Lake Biwa, a positive relationship was noted for temperature and light intensity with regard to the primary production rate (31,33). However, temperature increases also lead to increases in heterotrophic microbes and their rates of respiration (34).…”
Section: Lake Water Analysesmentioning
confidence: 99%